Shade, irrigation and variety effects upon bronzing responses of dry beans in Colorado - Schwartz, Howard F.; Ballarin, M.; Riggle, R.L. (1984)
Bronzing was observed in many of the bean trials conducted at Fort Collins (Colorado, USA) during 1982 to study the influence of water and shading stress on photosynthesis and protein content of 3 dry bean var., Roza, Pinto U.I. 111, and Olathe. Bronzing symptoms appeared during the late flowering and pod formation stages. A scale of 1-5 was used with 1 as no bronzing and 5 as severe bronzing (more than 50 percent leaf area bronzed). Results suggest that bronzing severity increased when plants were shaded and decreased when plants were under moisture stress. These treatment trends occurred at a similar rate for the 3 var., but the degree of bronzing was influenced by the var. Irrigation and shade treatments apparently influenced stomatal opening and the length of exposure to pollutants. (CIAT)